2021
DOI: 10.1332/239788221x16208334299524
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable care: theorising the wellbeing of caregivers to older persons

Abstract: The term ‘care crisis’ is invoked to denote chronic system failures and bad outcomes for the people involved. We present a comprehensive wellbeing framework and illustrate its practicality with evidence of negative outcomes for those who provide care. We find evidence of substantial material and relational wellbeing failures for family carers and for care workers, while there has been little interest in carers’ views of their ability to live the life that they most value. Understanding and improving wellbeing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 78 publications
1
24
0
1
Order By: Relevance
“…All expert groups interviewed viewed the use of mainstream digital devices in adult social care largely positively, though with some important caveats. Using a three-dimensional model of wellbeing as the conceptual lens through which to explore mainstream technologies' potential role in adult social care systems [40,41], we now reflect on the implications of this emerging area of practice for each dimension in turn.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All expert groups interviewed viewed the use of mainstream digital devices in adult social care largely positively, though with some important caveats. Using a three-dimensional model of wellbeing as the conceptual lens through which to explore mainstream technologies' potential role in adult social care systems [40,41], we now reflect on the implications of this emerging area of practice for each dimension in turn.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, subjective wellbeing is central to the Care Act, which states each person is best placed to define their own wellbeing. The Care Act's approach to wellbeing also aligns with research and theory, which has drawn together concepts of wellbeing from across the world to argue that the concept has three dimensions: "what a person has (the material), what they can do through their relationships with others (the relational) and how they feel and evaluate what they have and can do (the subjective)" [41] (p. 4). The relative importance of the dimensions is an area of contestation [38] with Austin [39] (p. 97), who argues for the core importance of relational wellbeing-"sociality" and "good social relationships"-as the "catalyst for overall wellbeing".…”
Section: The Sustainability Of Technology In Adult Social Care: Time ...mentioning
confidence: 99%
See 1 more Smart Citation
“…This perspective is grounded in human ecological assumptions that people have various capacities to act upon or adapt their environments and that person-environment fit occurs when environmental demands and opportunities are balanced with individual capabilities and resources (Bigonnesse and Chaudhury 2020 ). Two further assumptions illustrate its’ values base: that responsibility for supporting those with limited agency must be shared; and that a goal is to identify and create evidence of those who are rendered invisible by contexts that exclude (Keating et al 2021a , b ).…”
Section: Framing the Research Agendamentioning
confidence: 99%
“…Incorporating knowledge of diversity in areas such as ambiguous or exploitive family relations or decreased friend networks in the face of illness and death are examples. A systematic review of wellbeing of family caregivers found that material resources (including labour force participation and care-related out of pocket expenses); and relational resources (including with the cared-for person, other family members, friends and co-workers) are most important (Keating et al 2021a , b ). There is merit in further empirical examination of what are the core resources and relationships in their lives.…”
Section: Framing the Research Agendamentioning
confidence: 99%